SISTEM INFORMASI DARURAT PADA MINI MARKET MENGGUNAKAN MIKROKONTROLER ESP8266 BERBASIS INTERNET OF THINGS - Anugrah Deris (KOMPUTASI, 2019)
Increasing levels of crime have encouraged instrumentation and technology systems to deal with and expose crime cases. Emergency information systems on the mini market use ESP8266 microcontroller and have been built and analyzed to overcome this on the basis of the Internet of Things. Signals generated from this tool at shopping centers provide emergency information on the Website of the security unit. The results of the system test produced 3.6 seconds delay for power supply connections to NodeMcu. while the delay to calculate the Transmission (response signal) of the Security Unit, and the delay for the time the alarm sounds is 0 seconds. In this system, the website can receive information in the form of coordinate points and Minimarket addresses